Preferential Flow in Different Soil Architectures of a Small Karst Catchment - Wang, F. (2020)
The results showed that macropores and cracks were the major channels that resulted in a high degree of PF in depressions and downslope locations. Preferential flow also continued along the rock–soil interface in the downslope locations. Finger flow mainly appeared in mid‐ and upslope locations, and cracks mainly appeared in the surface soil layer. However, down‐ and upslope locations showed lower PF. We observed that PF might not contribute to the different infiltration rates in different topographical locations. Tillage in depressions damages macropores, thereby minimizing vertical percolation. The high saturated hydraulic conductivity (Ks) of the soil matrix covered the development of PF in the mid‐ and upslope locations, and the decrease in Ks weakened the formation of PF as a result of heterogeneity of soil properties. These findings demonstrate that infiltration‐excess runoff may occur in depressions and downslope locations and that saturation‐excess runoff may occur in mid‐ and upslope locations.